The influence of problem-based-blended learning assisted with computer simulation on students' critical thinking skills - Oktafiana, Eka; Widiyatmoko, Arif (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
This study aims to determine the effect of Problem Based-Blended Learning (PBL) assisted by computer simulations on critical thinking skills and to determine student responses after learning. This type of research is quasi-experimental with a nonequivalent control group design. The research sample was taken using a saturated sampling technique, with VII D as the experimental class and VIIC as the control class. Data collection techniques in this study include multiple choice with reasons to measure critical thinking skills and student response questionnaires. The influence of PBBL assisted by computer simulations on critical thinking skills can be seen in the t-test and N-Gain test results. The t-test results obtained a value of tcount > t table or 5,616 > 1,998, indicating a significant difference in students' critical thinking skills. The results of the N-Gain test in the experimental class got a value of 0.668 and 0.468 in the control class, so both classes were in the medium category. The results of this study were supported by 83.05% positive responses from students in the outstanding category. The results of this study indicate that computer simulation-assisted PBBL affects students' critical thinking skills.